Performance optimization design for constructed wetland coupled with microbial fuel cell for rural domestic sewage treatment - Tuodi Zhang; Songtao Shen; Yingyi Xu (PLoS ONE, 2026)
A vertical-flow constructed wetland-microbial fuel cell (CW-MFC) was established with Acorus calamus as the wetland vegetation for rural domestic wastewater treatment under low-temperature winter conditions. Response surface methodology (RSM) coupled with central composite design (CCD) was used to optimize three key electrode parameters: electrode plate projection coefficient (PC), inter-electrode distance (ID), and external resistance (ER), and to evaluate their effects on COD removal efficiency. Compared with the standalone constructed wetland (CW), the CW-MFC system significantly improved wastewater treatment performance: the effluent COD concentration of the CW was 66.14 mg/L, exceeding the first-class discharge limit (60.00 mg/L) specified in the “Water Pollutant Discharge Standard for Rural Domestic Sewage Treatment Facilities” (DB51/2626–2019). In contrast, the effluent COD concentrations of the CW-MFC system ranged from 18.81 to 54.06 mg/L, all meeting the aforementioned first-class standard, with a significantly higher COD removal rate than the CW (P < 0.05). After electrode parameter optimization, the optimal configuration was determined as PC = 0.33, ID = 272.94 mm, and ER = 1619.31 Ω. Under these optimized conditions, the CW-MFC system achieved a COD removal efficiency of 89.14%, which was consistent with the model-predicted value (88.06%) with a deviation of <1.2%. This confirmed that electrode parameter optimization effectively enhanced the treatment performance of the CW-MFC system. These findings could contribute new perspectives to the performance optimization of CW-MFC systems applied to decentralized rural domestic sewage treatment, particularly under low-temperature winter scenarios.